Wave Propagation with Human Body Communications in BANs - Ahmed, Doaa; Kirchner, Jens; Fischer, Georg (2017 IEEE MTT-S International Conference on Numerical Electromagnetic and Multiphysics Modeling and Optimization for RF, Microwave, and Terahertz Applications (NEMO), 2017)
Today's interest in health assistance systems, sport activities and remote patient monitoring require distributing various types of sensors at specific places across the human body. These sensors might be used to measure temperature, blood pressure level, blood glucose level and the like. This implies collecting the data generated at the distributed sensors in a wireless Body Area Network (BAN) and fusing these data at a central processing unit, which transfers the data, if needed, to a hospital or medical center for diagnosing. Whereas, transmission could be done for real time or stored data depending on the application scenario. However, sending data wirelessly is typically a very energy intensive task implying large batteries. Hence, BAN networks have been developed by IEEE 802.15.Task Group (TG6) to serve a variety of applications including medical, consumer lifestyle and entertainment applications at low power consumption. Human Body Communication is a non-RF propagation system in BAN network that utilizes the human body as a transmission medium to transfer data between several points inside, on or sometimes near the human body using electrodes, rather than antennas based on near field communication and quasistatic field approximations.
Keywords: Body Area Communication; Galvanic Coupling; Human Arm Model